Complications, Re-Intervention Rates, and Natural History of Residual Stone Fragments After Percutaneous Nephrolithotomy - Emmott, Anthony S; Brotherhood, Hilary L; Paterson, Ryan F; Lange, Dirk; Chew, Ben H (Journal of endourology, 2018)
The management of residual fragments (RFs) that persist after percutaneous nephrolithotomy (PCNL) has been poorly studied. Fragments have the potential to grow or cause symptoms. The aim of this study was to follow patients with fragments after PCNL to identify predictors of stone-related events (re-interventions and complications) after PCNL. Data were retrospectively collected from patients who underwent surgery from 2008 to 2013 at our hospital. Patients with fragments of any size on postoperative day 1 computed tomography of the kidney, ureter, and bladder radiograph (CT-KUB) were included, and patients with planned secondary interventions were excluded. Subgroup analysis was performed on subjects with CT-plain X-ray to determine fragment growth or passage. Of the 658 patients who received a postoperative CT-KUB on day 1, 299 patients (45%) had fragments that were 1 mm or larger. From this, 263 patients met the study criteria and were included. The size of fragments, using a 4 mm cutoff, did not predict the passage of fragments (p = 0.173) or growth (p = 0.572). On multivariable logistic regression analysis, previous history of renal stones and size of fragment were found to be predictive for stone-related events (p = 0.002 and 0.027, respectively). Kaplan-Meier analysis identified patients with fragments >4 mm having a shorter survival time before the occurrence of stone-related events (p = 0.044). The true stone-free rate was 55% after PCNL. However, 82.5% were stone free or had RFs 4 mm or less, which correlates with previous studies. Larger RFs had higher rates of stone-related events and shorter time to occurrence of stone-related events. The growth and spontaneous passage of RFs was independent of RF size, emphasizing the importance of obtaining a stone-free status after PCNL.